Pelaksanaan Eksekusi Objek Jaminan Gadai dengan Akad Rahn di Pegadaian Syariah Cabang Babakan Surabaya - Aisyah, Tiara Putri; Caesar Purwanto, Aldira Mara Ditta (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, Islamic financial institutions like Pegadaian Syariah Cabang Babakan Surabaya should conduct the execution of pledged collateral through the akad rahn fairly and in accordance with sharia principles, with clients understanding and fulfilling their payment obligations on time. However, in reality, there is a significant level of default among clients who do not fully understand the content and consequences of the contract, leading to delays or inability to repay loans on time. This study employs an empirical juridical method with conflict and stratification approaches to understand the execution of pledged collateral and identify the obstacles and solutions. The results indicate that Islamic pawning, conducted through akad rahn and ijarah, as stipulated by DSN-MUI Fatwa No. 25/DSN-MUI/III/2002, with a loan repayment period limited to 120 days, is not comprehensively understood by clients. This results in suboptimal understanding and awareness of the akad rahn and the auction execution process, especially when compounded by fluctuating market conditions. Despite clear regulations, the number of collateral objects auctioned each year remains significant, highlighting the need for more intensive education and more effective promotional strategies to address these challenges.